Police legitimacy and procedural justice among young Brazilian adolescents: A cross-sectional and time-ordered analysis - Rodrigues, Herbert Simões (The British journal of criminology, 2021)
The legal socialization framework expounds individual attitudes towards authority. The current study tested whether the attitudes of Brazilian adolescents towards social authorities (parents and teachers) explain later attitudes towards legal authority (the police). Data were obtained from three waves of a longitudinal study of Brazilian youth in São Paulo (ages 11-13; 50 per cent female) between 2016 and 2018. The time-ordered data are uniquely capable of testing the legal socialization framework as adolescent social spheres expand beyond the domestic domain. The findings of the structural equation models support the claim that attitudes towards social authorities explain later attitudes towards legal authority. The findings also paint a more complicated and nuanced picture of how spheres of authority are related.